Optimised accelerated solvent extraction of hexahydro-1,3,5-trinitro-1,3,5 triazine (RDX) from polymer bonded explosives - Ladyman, Melissa K.; Mai, Nathalie; Temple, Tracey; Coulon, Frederic (Cranfield University, 2018)
Raw HPLC data and calibration curves used to determine extraction efficiency of varying methods. The analysed data and produced graphs are also given. Numbers given are for % recovery of explosive (RDX or HMX) by extraction method/ optimized condition (ASE/ Sohxlet).
Keywords: 'RDX'; 'ASE method'; 'pressurised solvent extraction'; 'Soxhlet extraction'; 'PBX'; 'Analytical Chemistry not elsewhere classified'